(untitled) (Jagannath University Journal of Arts, 2026)
Festivals related to harvest, arrival of new crops, agricultural production and marketing have been celebrated for a long time in agrarian societies. It has emerged that agricultural festivals are not only a means of entertainment; they also play a role as a driving force for the local economy. As like as farming community Bogra districts people also celebrate various folk festivals related to agriculture for ages. The study was conducted using a qualitative research method, where various documents, research articles and references were reviewed. The study revealed that 10 festivals of Bagura district such as Nababarsha, Nabanna, Paush Parvan, Poradaha Mela, Khauro Mela and Goyal Puja are directly related to agriculture. It can be said that initiatives need to be taken to maintain the connection between folk festivals and the agricultural economy. This tradition can be preserved and revived through the concerted efforts of local administration, culture-loving people and the farming community. Jagannath University Journal of Arts, v-15, i-01, 2025:p75-90